Arsenic removal from water using flame-synthesized iron oxide nanoparticles with variable oxidation states - Abid, Aamir D. (2012)
We utilized gas-phase diffusion flame synthesis, which has potential for large-scale production of metal oxide nanoparticles, to produce iron oxide nanoparticles (IONPs) with variable oxidation states. The efficacy of these materials in removal of arsenate (As(V) ) from water was assessed. Two different flame configurations, a diffusion flame (DF) and an inverse diffusion flame (IDF), were employed to synthesize six different IONPs by controlling flame conditions. The IONPs produced in the IDF configuration (IDF-IONPs) had smaller particle diameters (4.8 – 8.2 nm) and larger surface areas (141–213 m(2)/g) than the IONPs produced in the DF configuration (29 nm, 36 m(2)/g), which resulted in their higher adsorption capacities. As(V) adsorption capacities of the IDF-IONPs increased when the IONPs were synthesized in more oxidizing conditions. The fully oxidized IDF-IONPs, maghemite (γ-Fe(2)O(3)), showed the highest As(V) adsorption capacity, comparable to that of magnetite nanocrystals synthesized by thermal decomposition of iron pentacarbonyl and equivalent to three to four times higher capacity than that of a commonly used goethite-based adsorbent. All IONPs were magnetically responsive, which is of great importance for solid−liquid separation. This study demonstrates that the IONPs synthesized in gas-phase flame, particularly IDF-IONPs, are excellent adsorbents because of their high As(V) sorption capacity, potential for large-scale production, and useful magnetic property.